Revitalisasi Tepian Sungai (Riverside) Taman Jalur Sesuai dengan Kaidah Lokal sebagai Sarana Interaksi Sosial (Kota Teluk Kuantan) - Zulhendri Zulhendri; Yusmar Yusuf; Swis Tantoro (Universitas Batanghari Jambi, 2023)
This study aims to determine the plan for revitalizing the riverside of the Park Lane in accordance with local norms as a means of social interaction. The subjects of this study consisted of 12 people, namely the Regent, all heads of the Culture, Environment, Communication and Information services, the Kuantan Singingi Cooperative, Bappeda, PUPR, LAMR, UMKM, and the local community of Kuantan Singingi Regency. The result of this research is that the plan for the revitalization of the Riverbanks of the Kuantan Singingi Regency Pathway Park is prepared in accordance with the local rules of the local area, where this Park will become a center for social interaction which includes cooperation, conflict, accommodation and acculturation between visitors and the Pathway Park manager. As well as the impact of this revitalization will affect the community's economic growth, public education, and there is a possibility of mixing cultures that enter from outside the area, and can improve environmental quality.